Comprehensive utilization process of kaolin tailings
By scrubbing and grading the kaolin tailings, the problems of low yield and poor product indicators in the existing technology are solved, and efficient and low-cost kaolin tailings recycling quartz sand is achieved, and higher yield and higher quality photovoltaic glass sand is obtained.
Patent Information
- Application Number
- CN202411623820.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-07
AI Technical Summary
In the comprehensive utilization of kaolin tailings, the yield is low and the product indicators fail to meet the requirements of photovoltaic glass sand, and mixed particle-grade grinding results in low quality of fine sand, which increases the difficulty of purification.
After high concentration scrubbing, the large particles of +5mm are directly discarded, and 2-5mm and 0.1-2mm are subjected to separate grinding treatments. The native -0.1mm and the -0.1mm produced by grinding are treated separately to obtain high-quality graded fine sand and photovoltaic glass sand.
The yield and product indicators of quartz sand in kaolin tailings have been improved, and the yield and quality of the photovoltaic glass sand obtained is higher, which increases the added value of the product.
Smart Images

Figure CN119565765A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of deep processing of non-metallic minerals, and in particular to a comprehensive utilization process of kaolin tailings. Background Art
[0002] Kaolin is a hydrous aluminum silicate composed of a variety of minerals, the basic mineral components of which are clay minerals such as kaolinite and halloysite. Kaolin has excellent physical and chemical properties such as plasticity, dispersibility, suspension, electrical insulation, fire resistance, high whiteness, low hardness and acid resistance, making it widely used in ceramics, papermaking, coatings, plastics, rubber, chemicals, petroleum refining, electronics, paints, inks, refractory materials, medicine, cosmetics, pesticides, metallurgy, military industry, aerospace and other fields.
[0003] my country has few high-quality kaolin resources. Most of the kaolin ores are associated with a variety of minerals, especially the sandy kaolin in the south, whose mineral composition is generally composed of kaolinite, quartz, feldspar, mica and a small amount of metal minerals. The yield of sandy kaolin tailings is 70% to 80%. The production process of kaolin produces tens of millions of tons of kaolin tailings, which is increasing year by year. The storage of a large amount of kaolin tailings pollutes the environment, destroys the ecological balance, and causes a waste of resources.
[0004] The comprehensive utilization of kaolin tailings is mainly to comprehensively recover quartz, mica, feldspar and other minerals in kaolin tailings. With the rapid development of photovoltaic new energy industry, the demand for high-quality photovoltaic glass sand has increased significantly. Purifying and processing kaolin tailings to prepare photovoltaic glass sand has become a research hotspot. Prior art CN112892852B discloses "a method for preparing silica sand for photovoltaic glass from kaolin tailings" to process and purify the 1-5mm particle size in kaolin tailings to obtain silica sand SiO299.5-99.7%, Al2O30.1-0.2%, Fe2O30.0090-0.010%, but the yield is only 14%-18%; Prior art CN110201791B discloses "a method for comprehensive utilization of sandy kaolin tailings containing tourmaline, muscovite and quartz sand" to obtain quartz sand for ordinary flat glass, which fails to meet the index requirements of photovoltaic glass sand.
[0005] In the existing technology, all the mixed particle sizes of kaolin tailings are usually put into grinding, the -0.6mm grinding product is deslimed, and the 0.1-0.6mm particle size is purified and recovered by magnetic separation, flotation, acid leaching and other processes. On the one hand, the mixed particle size grinding will make the -0.1mm particle size fine sand have complex components, low quality and low comprehensive utilization value; on the other hand, the large particles with serious iron contamination of +5mm particle size are put into 0.1-0.6mm, which increases the difficulty of purification.
[0006] Therefore, in order to solve the above problems, the present invention provides a comprehensive utilization process of kaolin tailings to achieve more efficient and low-cost recovery of quartz sand from kaolin tailings, and obtain a product with higher yield and better product indicators. Summary of the invention
[0007] The purpose of the present invention is to provide a comprehensive utilization process of kaolin tailings to achieve high-value utilization of kaolin tailings.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A comprehensive utilization process of kaolin tailings comprises the following steps:
[0010] (1) Scrubbing of kaolin tailings;
[0011] (2) The scrubbed kaolin slurry is passed through a 5 mm linear sieve, the +5 mm waste rock is used as sand and gravel, and the -5 mm is classified into 2-5 mm, 0.1-2 mm and -0.1 mm;
[0012] (3) 2-5mm particle size grinding and classification, +0.6mm is returned for re-grinding, -0.6mm is classified to remove -0.045mm tailings, 0.045-0.6mm is subjected to a first-stage magnetic separation to obtain a magnetic concentrate, the magnetic concentrate is subjected to 1-2 stages of strong magnetic separation to obtain a strong magnetic concentrate, the strong magnetic concentrate is heated and washed with chemicals, and after washing, the chemicals are removed and mud is washed to obtain first-grade photovoltaic glass sand and graded fine sand;
[0013] (4) The 0.1-2mm particle size is graded, +0.6mm is ground and screened until all are ground to -0.6mm, -0.6mm is subjected to spiral chute gravity separation to obtain heavy minerals and light minerals, the light minerals are subjected to 2-3 stages of magnetic separation to obtain magnetic concentrate, the magnetic concentrate is floated to obtain mica, the foam product is a fine mica product, the product in the flotation tank is graded and deslimed, the -0.1mm particle size is graded into fine sand, the fine sand is a raw material for daily-use ceramics or glass fiber; the 0.1-0.6mm particle size is heated and medicated for scrubbing, and after scrubbing, it is demedicated and deslimed to obtain secondary photovoltaic glass sand.
[0014] Preferably, in step (1), the kaolin tailings are scrubbed at a concentration of 50% to 60% and the scrubbing time is 10 to 30 minutes.
[0015] Preferably, in step (2), the -0.1mm after -5mm classification is the original -0.1mm tailings, which mainly include kaolinite, feldspar, mica, quartz, etc., and can be used for building ceramics.
[0016] Preferably, in step (3), the magnetic separation intensity is 0.5-0.7T; the strong magnetic separation intensity is 1.2-1.4T.
[0017] Preferably, in step (3), the scrubbing temperature of the strong magnetic concentrate for heating and scrubbing with chemicals is 50°C to 80°C, the scrubbing concentration is 50% to 60%, the scrubbing time is 2 to 4 hours, the scrubbing agent is selected from one or more of H2SO4, HF, H2C2O4, and HCl, and the total acid dosage is 5 to 15 kg / t.
[0018] Preferably, in the step (3), the SiO2 content of the first-level photovoltaic glass sand is greater than 99.5%, and the Fe2O3 content is less than 50 ppm; the SiO2 content of the graded fine sand is greater than 99%, and the Fe2O3 content is less than 200 ppm, and the fine sand can be further processed into a silicon micropowder product.
[0019] Preferably, in step (4), heavy minerals such as rutile, ilmenite, zircon, tourmaline, etc. are comprehensively recovered.
[0020] Preferably, in step (4), the magnetic separation intensity is 0.5-1.6 T; the pH value of the magnetic concentrate slurry is adjusted to 3-4 with sulfuric acid; and mica is floated with dodecylamine, with the dosage of dodecylamine being 100-300 g / t.
[0021] Preferably, in step (4), the scrubbing temperature of the 0.1-0.6 mm particle size heated and medicated scrubbing is 50-80°C, the scrubbing concentration is 50%-60%, the scrubbing time is 3-5 hours, the scrubbing agent is selected from one or more of H2SO4, HF, H2C2O4, HCl, and the total acid dosage is 10-30kg / t.
[0022] Preferably, in step (4), the SiO2 content of the secondary photovoltaic glass sand is greater than 99.3%, and the Fe2O3 content is 80-100 ppm.
[0023] Due to the application of the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0024] The kaolin tailings of the present invention are firstly scrubbed at a high concentration and then classified after scrubbing, and large particles of +5mm with a high iron content are directly discarded; 2-5mm and 0.1-2mm are separately ground to obtain quartz sand of different grades; original -0.1mm and -0.1mm produced by grinding are separately processed to obtain high-quality classified fine sand, thereby increasing the added value of the product; and the classification process can obtain a higher photovoltaic sand yield and a higher-quality photovoltaic sand product. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, some of the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be made based on these drawings without paying any creative work.
[0026] Figure 1 This is a process flow chart of comprehensive utilization of kaolin tailings according to Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.
[0028] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0029] Example 1
[0030] See attached Figure 1 This embodiment provides a comprehensive utilization process of kaolin tailings. This embodiment is a kaolin tailings in Guangdong. The ore contains 90% quartz, 2% kaolinite, 4% feldspar, 3% mica, and 1% others. The process specifically includes the following steps:
[0031] (1) kaolin tailings are scrubbed at a scrubbing concentration of 55% and a scrubbing time of 30 min;
[0032] (2) The scrubbed kaolin slurry is passed through a 5 mm linear sieve, the +5 mm waste rock is used as sand and gravel, and the -5 mm is classified into 2-5 mm, 0.1-2 mm and -0.1 mm. The -0.1 mm is mainly kaolinite, feldspar, mica, quartz, etc.;
[0033] (3) 2-5mm particle size grinding and classification, +0.6mm is returned for regrinding, -0.6mm is classified to remove -0.045mm tailings, 0.045-0.6mm is subjected to a first-stage magnetic separation to obtain a magnetic concentrate, and the magnetic separation intensity is 0.7T; the magnetic concentrate is subjected to two-stage strong magnetic separation to obtain a strong magnetic concentrate, and the strong magnetic separation intensity is 1.4T; the strong magnetic concentrate is heated and medicated for scrubbing, the scrubbing temperature is 70°C, the scrubbing concentration is 55%, the scrubbing time is 3 hours, the scrubbing agent is selected from one or more of H2SO4, HF, H2C2O4, HCl, and the total acid dosage is 10kg / t; after scrubbing, the drug removal and mud removal washing are carried out to obtain first-class photovoltaic glass sand and graded fine sand;
[0034] (4) The 0.1-2mm particle size is graded, +0.6mm is ground and screened until all are ground to -0.6mm, and -0.6mm is subjected to spiral chute gravity separation to obtain heavy minerals and light minerals. The heavy minerals are comprehensively recovered as rutile, ilmenite, zircon, tourmaline, etc. The light minerals are subjected to three-stage magnetic separation to obtain magnetic separation concentrate, the first stage magnetic separation intensity is 0.7T, and the second to third stages magnetic separation intensity is 1.4T; the magnetic separation concentrate is slurried with sulfuric acid at pH = 4, and the magnetic separation concentrate is flotated to obtain Mica, the foam product is a fine mica product, the product in the flotation tank is graded and deslimed, -0.1mm particle size is graded fine sand, the fine sand is daily ceramic or glass fiber raw material; 0.1-0.6mm particle size is heated and medicated for scrubbing, the scrubbing temperature is 70℃, the scrubbing concentration is 55%, the scrubbing time is 5 hours, the scrubbing agent is H2SO4+H2C2O4, and the total acid dosage is 20kg / t; after scrubbing, the drug removal and desliming washing are carried out to obtain secondary photovoltaic glass sand;
[0035] In this embodiment, the first-level photovoltaic sand yield is 11.87%, the SiO2 content is 99.7%, and the Fe2O3 content is 35ppm. The second-level photovoltaic sand product yield is 52.87%, the SiO2 content is 99.3%, and the Fe2O3 content is 90ppm.
[0036] Example 2
[0037] This embodiment provides a comprehensive utilization process of kaolin tailings. This embodiment is a kaolin tailings in Guangxi. The ore contains quartz content of 87%, kaolinite content of 2%, feldspar content of 3%, mica content of 7%, and other content of 1%. The process specifically includes the following steps:
[0038] (1) The kaolin tailings are scrubbed at a scrubbing concentration of 60% and a scrubbing time of 20 min;
[0039] (2) The scrubbed kaolin slurry is passed through a 5 mm linear sieve, the +5 mm waste rock is used as sand and gravel, and the -5 mm is classified into 2-5 mm, 0.1-2 mm and -0.1 mm. The -0.1 mm is mainly kaolinite, feldspar, mica, quartz, etc.;
[0040] (3) 2-5mm particle size grinding and classification, +0.6mm is returned for re-grinding, -0.6mm is classified to remove -0.045mm tailings, 0.045-0.6mm is subjected to a first-stage magnetic separation to obtain a magnetic concentrate, and the magnetic separation intensity is 0.6T; the magnetic concentrate is subjected to two-stage strong magnetic separation to obtain a strong magnetic concentrate, and the strong magnetic separation intensity is 1.4T; the strong magnetic concentrate is heated and medicated for scrubbing, the scrubbing temperature is 70°C, the scrubbing concentration is 55%, the scrubbing time is 3 hours, the scrubbing agent is HF+H2C2O4, and the total acid dosage is 9kg / t; after scrubbing, the drug removal and mud removal washing are carried out to obtain first-class photovoltaic glass sand and graded fine sand;
[0041] (4) 0.1-2mm particle size is classified, +0.6mm is ground and screened until all are ground to -0.6mm, -0.6mm is subjected to spiral chute gravity separation to obtain heavy minerals and light minerals, heavy minerals are comprehensively recovered as rutile, ilmenite, zircon, tourmaline, etc., and light minerals are subjected to two-stage magnetic separation to obtain magnetic separation concentrate, and the magnetic separation intensity is 1.3T; the magnetic separation concentrate is slurried with sulfuric acid to pH=3, and the magnetic separation concentrate is floated to obtain mica, and the foam product is a fine mica product. The product in the flotation tank is graded and deslued, and -0.1mm particle size is graded as fine sand, and the fine sand is a raw material for daily-use ceramics or glass fibers; 0.1-0.6mm particle size is heated and medicated for scrubbing, the scrubbing temperature is 70°C, the scrubbing concentration is 55%, the scrubbing time is 5 hours, the scrubbing agent is H2SO4, and the total acid dosage is 18kg / t; after scrubbing, de-medication and de-sludging washing is performed to obtain secondary photovoltaic glass sand;
[0042] In this embodiment, the first-level photovoltaic sand yield is 13.56%, the SiO2 content is 99.5%, and the Fe2O3 content is 50ppm; the second-level photovoltaic sand product yield is 46.78%, the SiO2 content is 99.3%, and the Fe2O3 content is 90-100ppm; the mica product yield is 7.45%, the K2O content is 9.43%, and the Fe2O3 content is 1.45%.
[0043] Example 3
[0044] This embodiment provides a comprehensive utilization process of kaolin tailings. This embodiment is a kaolin tailings from Australia. The quartz content in the original ore is 92%, kaolinite is 3%, mica is 5%, and other 1%. The process specifically includes the following steps:
[0045] (1) kaolin tailings are scrubbed at a scrubbing concentration of 55% and a scrubbing time of 30 min;
[0046] (2) The scrubbed kaolin slurry is passed through a 5 mm linear sieve, the +5 mm waste rock is used as sand and gravel, and the -5 mm is classified into 2-5 mm, 0.1-2 mm and -0.1 mm. The -0.1 mm is mainly kaolinite, feldspar, mica, quartz, etc.;
[0047] (3) 2-5mm particle size grinding and classification, +0.6mm is returned for re-grinding, -0.6mm is classified to remove -0.045mm tailings, 0.045-0.6mm is subjected to a first-stage magnetic separation to obtain a magnetic concentrate, and the magnetic separation intensity is 0.5T; the magnetic concentrate is subjected to two-stage strong magnetic separation to obtain a strong magnetic concentrate, and the strong magnetic separation intensity is 1.4T; the strong magnetic concentrate is heated and medicated for scrubbing, the scrubbing temperature is 70°C, the scrubbing concentration is 60%, the scrubbing time is 3 hours, the scrubbing agent is H2C2O4, and the total acid dosage is 10kg / t; after scrubbing, the drug removal and mud removal washing are carried out to obtain first-class photovoltaic glass sand and graded fine sand;
[0048] (4) The 0.1-2mm particle size is graded, +0.6mm is ground and screened until all are ground to -0.6mm, and -0.6mm is subjected to spiral chute gravity separation to obtain heavy minerals and light minerals. The heavy minerals are comprehensively recovered as rutile, ilmenite, zircon, tourmaline, etc. The light minerals are subjected to three-stage magnetic separation to obtain magnetic separation concentrate. The magnetic field strength of the first stage is 0.5T, and the magnetic separation strength of the second to third stages is 1.2T; the magnetic separation concentrate is slurried with sulfuric acid at pH = 4, and the magnetic separation concentrate is floated to obtain To mica, the foam product is a fine mica product, the product in the flotation tank is graded and deslimed, -0.1mm particle size is graded fine sand, the fine sand is daily ceramic or glass fiber raw material; 0.1-0.6mm particle size is heated and medicated for scrubbing, the scrubbing temperature is 70℃, the scrubbing concentration is 55%, the scrubbing time is 5 hours, the scrubbing agent is H2SO4+H2C2O4, and the total acid dosage is 19kg / t; after scrubbing, the drug removal and desliming washing are carried out to obtain secondary photovoltaic glass sand;
[0049] In this embodiment, the first-level photovoltaic sand yield is 20.56%, the SiO2 content is 99.5%, and the Fe2O3 content is 45ppm; the second-level photovoltaic sand product yield is 48.33%, the SiO2 content is 99.4%, and the Fe2O3 content is 80-100ppm; the mica product yield is 4.78%, the K2O content is 9.07%, and the Fe2O3 content is 2.45%.
[0050] Comparing the above embodiments with the prior art, the product yield obtained by the present invention is higher and the product index is better.
[0051] In summary, the kaolin tailings of the present invention are firstly scrubbed at a high concentration and then classified after scrubbing, and large particles with a high iron content of +5mm are directly discarded; 2-5mm and 0.1-2mm are separately processed by grinding to obtain quartz sand of different grades; the original -0.1mm and the -0.1mm produced by grinding are separately processed to obtain high-quality classified fine sand, thereby increasing the added value of the product; the classification treatment can obtain a higher photovoltaic sand yield and a higher quality photovoltaic sand product.
[0052] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A comprehensive utilization process of kaolin tailings, characterized in that: The steps include: (1) Scrubbing of kaolin tailings; (2) The scrubbed kaolin slurry is passed through a 5 mm linear sieve, the +5 mm waste rock is used as sand and gravel, and the -5 mm is classified into 2-5 mm, 0.1-2 mm and -0.1 mm; (3) 2-5mm particle size grinding and classification, +0.6mm is returned for re-grinding, -0.6mm is classified to remove -0.045mm tailings, 0.045-0.6mm is subjected to a first-stage magnetic separation to obtain a magnetic concentrate, the magnetic concentrate is subjected to 1-2 stages of strong magnetic separation to obtain a strong magnetic concentrate, the strong magnetic concentrate is heated and washed with chemicals, and after washing, the chemicals are removed and mud is washed to obtain first-grade photovoltaic glass sand and graded fine sand; (4) The 0.1-2mm particle size is graded, and the +0.6mm particle size is ground and screened until all the particles are ground to -0.6mm. The -0.6mm particle size is subjected to spiral chute gravity separation to obtain heavy minerals and light minerals. The light minerals are subjected to 2-3 stages of magnetic separation to obtain magnetic concentrate. The magnetic concentrate is floated to obtain mica. The products in the flotation tank are graded and deslimed. The -0.1mm particle size is graded as fine sand. The 0.1-0.6mm particle size is heated and washed with chemicals, and then washed with chemicals and deslimed to obtain secondary photovoltaic glass sand.
2. A kaolin tailings comprehensive utilization process as claimed in claim 1, characterized in that: In the step (1), the kaolin tailings are scrubbed at a scrubbing concentration of 50% to 60% and the scrubbing time is 10 to 30 minutes.
3. A kaolin tailings comprehensive utilization process as claimed in claim 1, characterized in that: In the step (2), the -0.1mm after -5mm classification is the original -0.1mm tailing mud, which mainly consists of kaolinite, feldspar, mica, quartz, etc.
4. A kaolin tailings comprehensive utilization process as claimed in claim 1, characterized in that: In the step (3), the magnetic separation intensity is 0.5-0.7T; the strong magnetic separation intensity is 1.2-1.4T.
5. A kaolin tailings comprehensive utilization process as claimed in claim 1, characterized in that: In the step (3), the scrubbing temperature of the strong magnetic concentrate for heating and chemical scrubbing is 50°C to 80°C, the scrubbing concentration is 50% to 60%, the scrubbing time is 2 to 4 hours, the scrubbing agent is selected from one or more of H2SO4, HF, H2C2O4, and HCl, and the total acid dosage is 5 to 15 kg / t.
6. A kaolin tailings comprehensive utilization process as claimed in claim 1, characterized in that: In the step (3), the SiO2 content of the first-grade photovoltaic glass sand is greater than 99.5%, and the Fe2O3 content is less than 50 ppm; the SiO2 content of the graded fine sand is greater than 99%, and the Fe2O3 content is less than 200 ppm, and the fine sand can be further processed into a silicon micropowder product.
7. A kaolin tailings comprehensive utilization process as claimed in claim 1, characterized in that: In the step (4), heavy minerals such as rutile, ilmenite, zircon, tourmaline, etc. are comprehensively recovered.
8. A kaolin tailings comprehensive utilization process as claimed in claim 1, characterized in that: In the step (4), the magnetic separation intensity is 0.5-1.6 T; the pH value of the magnetic concentrate is adjusted to 3-4 by sulfuric acid slurry; and dodecylamine is used for mica flotation, with the amount of dodecylamine used being 100-300 g / t.
9. A kaolin tailings comprehensive utilization process as claimed in claim 1, characterized in that: In the step (4), the scrubbing temperature of the 0.1-0.6 mm particle size heated and medicated scrubbing is 50-80° C., the scrubbing concentration is 50%-60%, the scrubbing time is 3-5 hours, the scrubbing agent is selected from one or more of H2SO4, HF, H2C2O4, and HCl, and the total acid dosage is 10-30 kg / t.
10. A kaolin tailings comprehensive utilization process as claimed in claim 1, characterized in that: In the step (4), the SiO2 content of the secondary photovoltaic glass sand is greater than 99.3%, and the Fe2O3 content is 80-100 ppm.
Citation Information
Patent Citations
Comprehensive Utilization Methods for Sandy Kaolin Tailings Containing Tourmaline, Muscovite, and Quartz Sand
CN110201791B
A method for preparing silica sand for photovoltaic glass from kaolin tailings
CN112892852B
Comprehensive utilization treatment process of kaolin tailings
CN109772578A
Comprehensive utilization method of sandy kaolin tailings containing tourmaline, muscovite and quartz sand
CN110201791A
Method for preparing silica sand for photovoltaic glass from kaolin tailings
CN112892852A
Cited By
Recycling system for secondary application of fine sand
CN120079513A
Comprehensive utilization process for kaolin tailings
WO2026103127A1